Social and behaviour change communication (SBCC) project in Manica, Mozambique: Baseline survey report - Mario Gyori; Tatiana Martínez Zavala; Jessica Baier; Maria Hernandez; Sofie Olsson; Alexis Lefevre (International Policy Centre for Inclusive Growth (IPC-IG), 2017)
This baseline report has been developed for an impact evaluation of a social and behaviour change communication (SBCC) project implemented by the World Food Programme (WFP) in Mozambique's Manica province and funded through the European Union's MDG1c initiative. The intervention's overall goal is to improve children's health and nutrition by promoting good practices in the areas of maternal care and nutrition, infant and young child feeding, malaria prevention, and water, sanitation and hygiene. The intervention builds on two components: i) interpersonal communication, consisting of the training of community health committee members who in turn train community members; and ii) mass media communication, consisting of short-duration radio spots, broadcast by community radio stations that participated in corresponding capacity development activities. Overall, the project is expected to reach around 44,640 individuals through the interpersonal communication component and 379,000 individuals through the mass media component. […]
Keywords: 330; Social; behaviour; change; communication; SBCC; project; Manica; Mozambique; baseline; survey; report